Regularity Estimates for Nonlinear Elliptic and Parabolic Problems Cetraro, Italy 2009 Editors: Ugo Gianazza, John Lewis - Lewis, John.; Lindqvist, Peter; Manfredi, Juan J.; Salsa, Sandro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The issue of regularity has played a central role in the theory of Partial Differential Equations almost since its inception, and despite the tremendous advances made it still remains a very fruitful research field. In particular considerable strides have been made in regularity estimates for degenerate and singular elliptic and parabolic equations over the last several years, and in many unexpected and challenging directions. Because of all these recent results, it seemed high time to create an overview that would highlight emerging trends and issues in this fascinating research topic in a proper and effective way. The course aimed to show the deep connections between these topics and to open new research directions through the contributions of leading experts in all of these fields.
Applications of Boundary Harnack Inequalities for p Harmonic Functions and Related Topics -- Regularity of Supersolutions -- Introduction to random Tug-of-War games and PDEs -- The Problems of the Obstacle in Lower Dimension and for the Fractional Laplacian.
Keywords: Mathematics; Differential equations, partial; Mathematical optimization; Mathematics; Partial Differential Equations; Calculus of Variations and Optimal Control; Optimization